3D brain tissue physiological model with co-cultured primary neurons and glial cells in hydrogels. (October 2020) - Raimondi, Ilaria; Tunesi, Marta; Forloni, Gianluigi; Albani, Diego; Giordano, Carmen
Recently, researchers have focused on the role of gut microbiota on human health and reported the existence of a bidirectional relationship between intestinal microbiota and the brain, referred to as microbiota-gut-brain axis (MGBA). In this context, the development of an organ-on-a-chip platform recapitulating the main players of the MGBA would help in the investigations of the biochemical mechanisms involved. In this work, we focused on the development of a new, hydrogel-based, 3D brain-like tissue model to be hosted in the brain compartment of the aforementioned platform. We previously cultured primary mouse microglial cells, cortical neurons and astrocytes independently, once embedded or covered by a millimeter layer of two selected collagen-based hydrogels. We evaluated cell metabolic activity up to 21 days, cell morphology, spatial distribution and synapse formation. Then, we exploited the best performing culturing condition and developed a more complex brain-like tissue model based on the co-culture of cortical neurons and glial cells in physiological conditions. The obtained results indicate that our 3D hydrogel-based brain tissue model is suitable to recapitulate in vitro the key biochemical parameters of brain tissue.